Sistem Pengendalian Suhu dan Kelembaban Kumbung Jamur Tiram secara Realtime Menggunakan Esp8266 - Arafat Arafat; Desy Ika Puspitasari; Wagino Wagino (Jurnal Fisika FLUX, 2019)
Oyster Mushroom is one of the high-value consumption mushrooms. The development of mushroom experienced rapid growth marked by the increasing number of farmers breeding mushroom is directly proportional to number of mushroom food business. The process of mushroom cultivation in mushroom’s greenhouse depends on physical factors such as temperature, humidity, light, pH of planting medium, and air aeration. Watering activity is done if the condition and humidity of mushroom's greenhouse was dry, three times a day at the morning, afternoon and evening. If the conditions of temperature and humidity fluctuate in the current seasons, it is not enough to be sprayed. High temperature and humidity fluctuations disturbed harvest. The results of this research are realtime temperature and humidity control system, esp8266 12-F and DHT22 sensor to read humidity value that can do watering and keep humidity greenhouse. The best humidity limit is 65% and maximum is 80%. If the humidity condition reaches 65%, then esp8266 will activate the relay to turn on the DC pump machine and nozzle spray. If humidity reached 80%, then esp8266 will turn off the DC pump. 80% humidity limit setting to avoid mushrooms from getting too wet. Humidity conditions monitored with android smartphone in realtime.